Human Stromal Cell Aggregates Concentrate Adipose Tissue Constitutive Cell Population by In Vitro DNA Quantification Analysis. Issue 6 (December 2020) - Sesé, Borja; Sanmartín, Javier M.; Ortega, Bernat; Llull, Ramon
Abstract : Background: Regenerative cell strategies rely on stromal cell implants to attain an observable clinical outcome. However, the effective cell dose to ensure a therapeutic response remains unknown. To achieve a higher cell dose, the authors hypothesized that reducing the volume occupied by mature adipocytes in lipoaspirate will concentrate the stromal vascular fraction present in the original tissue. Methods: Human standardized lipoaspirate ( n = 6) was centrifuged (1200 g for 3 minutes) and the water phase was discarded. Mechanical disaggregation was achieved by shearing tissue through 2.4- and 1.2-mm Luer-to-Luer transfers. After a second centrifugation (800 g for 10 minutes), stromal cell aggregates were separated from the supernatant oil phase. Lipoaspirate percentage composition was determined by its constituent weights. Cell content was measured by total DNA quantification, and partial cell viability was determined by image cytometry. Tissue sections were evaluated histologically (hematoxylin and eosin and Masson trichrome stains). Results: Stromal cell aggregates reduced the standardized lipoaspirate mass to 28.6 ± 4.2 percent. Accordingly, the cell density increased by 222.6 ± 63.3 percent (from 9.9 ± 1.4 million cells/g to 31.3 ± 6.6 million cells/g; p < 0.05). Cell viability was unaffected in stromal cell aggregates (71.3 ± 2.5 percent) compared to standardized lipoaspirate (72.2 ± 2.3 percent), and histologic analysis revealed high-density areas enriched with stromal cells (622.9 ± 145.6 percent) and extracellular matrix (871.2 ± 80.3 percent). Conclusion: Stromal cell aggregates represent a biological agent that triplicates the cell density versus unprocessed lipoaspirate, low on oil and water fluids, and enriched extracellular matrix components. Abstract : Supplemental Digital Content is available in the text.